Nouvelles données chronologiques, biologiques et alimentaires sur l'enfant Mésolithique de Verberie - Le Buisson Campin (Oise) - Françoise Audouze; Dorothée G. Drucker; Frédérique Valentin (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The skeleton of a child discovered on the site of Verberie (Oise) has been re-examined in detail in order to determine its chronological, biological and dietary status. Thus, direct dating by C14 (AMS), a re-examination of the burial and how it functioned, a morphological study and an analysis of the stable isotopes of the collagen were carried out. The date obtained, 8740 + 50 years BP (GrA-34097), enables chronological placement of the Verberie child in the eighth millennium (Mesolithic period), that is, a date earlier than that previously presumed (Chalcolithic period). The anthropological study confirms the estimation of age at death, between one and two years. The examination of the bone and dental development indicates the small stature of this child although it probably did not suffer any major physiological stress. The Verberie child died before weaning, according to the results of stable isotope analysis which indicate that the diet consisted exclusively of milk. These data are all supplementary elements in the knowledge of the biology of Mesolithic children.